The Neolithic of the U.S.S.R. (A Guide to the Recent Literature on the Subject) - Sulimirski, T. (1967)
University of London; 6 for 1966; spez. 109-113: The Caucasus — Northern Caucasus and Abkhasia – The Kyul-Tepe I culture – The Kura-Araxes culture – The Maikop culture; 124-127: Soviet Central Asia – Chorasmia; reiche Literaturangaben.